Privatisation of Life - Jurić, Hrvoje, filozof (2010)
In this presentation the author deals with the ethical and political aspects of the current trend of privatisation of life: the privatisation of particular spheres of social life, e.g. education and healthcare, as well as the privatisation of 'bare life', i.e. living beings and natural resources – the issue concerned, among the others, by Vandana Shiva in her books "Biopiracy" and "Water Wars". For this purpose, an outline of the context in which these issues should be considered is introduced (the prevailing technoscientific-economic-political system), along with the discussion on the concepts of property and private property (primarily supported by works of Jean-Jacques Rousseau and Karl Marx).
Projekt MZOS
ENG